Without a clue : a novel - Ferguson, Melissa, 1985- (Thomas Nelson, 2026)
Penelope Mae Dupont has one superpower: keeping her cool. Which is essential when you're the personal assistant to renowned mystery author Hugh Griffin. But when Pip organizes a luxury book cruise featuring The Fabulous Seven--a glittering cast of seven bestselling authors known for both their brilliance and their drama--her trademark composure starts slipping. One boat. Seven egos. Hundreds of fans. What could possibly go wrong? Well . . . murder, for starters.On day two, Hugh is found dead--and the cruise security team proves to be utterly incompetent. Stranded in the middle of the Atlantic with no help in sight, Pip realizes if anyone's going to solve the case, it'll have to be her. And so, with her friend and ally Nash, the dreamy Western author who's just as rugged as the cowboys he writes about, she puts her amateur sleuthing skills to the test. As Pip and Nash navigate an ocean of secrets, shocking twists, and one too many red herrings, she'll have to decide whether she's meant to stay behind the scenes--or finally step into the spotlight . . . and maybe, just maybe, find love along the way.